CHEMICAL AND SENSORY QUALITY CHARACTERISTICS OF CHICKEN NUGGET PRODUCTS SUBSTITUTED WITH MOCAF FLOUR (MODIFIED CASSAVA FLOUR): KARAKTERISTIK MUTU KIMIA DAN SENSORIS PRODUK NUGGET AYAM SUBTITUSI TEPUNG MOCAF (MODIFIED CASSAVA FLOUR) - Abdi, Yenny Febriana Ramadhan; Rochmah, Alfi Nur; Nurfadila, Irma Dwi; Faiz, Muhammad Nurul; Suleman, Dininurilmi Putri; Nadhilah, Dini; Zulfa, Fitriyah; Riski, Prajwalita Rukmakharisma (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
Diversification of processed chicken meat is a strategic step in utilizing its nutritional content and extending its shelf life. One of the diversifications of processed chicken meat is chicken nuggets. Generally, nuggets use wheat flour and tapioca as filler. The used of wheat flour can potentially cause health problems. In order to reduce dependence on the use of wheat flour, it can be replaced with mocaf flour. The aim of this research is to determine the effect of substituting wheat flour using mocaf flour in making chicken nuggets. The method used in this study used a Completely Randomized Design (CRD) with three treatments and three replications with a comparison of wheat flour and mocaf flour, namely F1 ( 100 g wheat flour), F2 (40 g mocaf flour:60 g wheat flour) and F3 (20 g mocaf flour:80 g wheat flour). The data obtained will be analyzed using the Analysis of Variance (ANOVA) test and to determine the real difference between treatments, it was continued with the Duncan Multiple Range Test (DMRT) with a significance level of 5%. The results obtained showed that F1 (100 g wheat flour) was preferred by panelists with a fat content of 1.62%, F2 (40 g mocaf flour: 60 g wheat flour) showed a moisture content (7.88%) and a fiber content (29.38%) higher and F3 (20 g mocaf flour: 80 g wheat flour) showed a higher ash content of 5.29%. Keywords: Chemical quality; Chicken nuggets; Sensory; Mocaf flour.